PENGARUH HARGA EMAS TERHADAP MINAT BERINVESTASI SYARIAH - Medina Mutiara, Dawiya; Fitri Yani, Dewi; Rafif Athaya, Muhammad (Maisyatuna, 2023)
This study aims to determine the effect of gold prices on investment intentions. The data analysis technique used is descriptive quantitative. With a sample of 50 respondents through purposive sampling method. The results of this study, namely the Correlation Coefficient test, obtained an rxy value of 0.710, meaning that the price of gold has a positive and strong effect on Islamic investment intentions. For the regression equation, Y = 9.423 + 0.710 X, where the price of gold has a significant influence on the interest of customers to invest using gold savings products. The value of the coefficient of determination (R2) is 0.552 or 55.2%, which means that the price of gold affects the interest of customers to invest in using gold savings products at PT. Pegadaian (Persero) Lubuk Pakam Branch Office. Knowing whether the hypothesis in this study is accepted or not, the t (partial) test is used which is obtained from the price of gold (x) which has a tcount of 4.581 > ttable of 2.010. Thus Ha is accepted because tcount>ttable. Therefore, it can be concluded that the price of gold partially has a significant effect on Islamic investment intentions.